The importance of games practiced by children from the perspective of teachers/children - Al-Hileh, Mohamed M.; Hamdan, Sara M.; Nasereddin, Hebah H. O. (Opción, 2020)
This study aimed at inquiring the advantages and disadvantages of electronic games practiced by children at the late childhood and adolescence stages, from teachers' and children’s point of view via comparative quantitative research methods. The findings revealed that both teachers and children from late childhood and adolescence stages agreed that there were a lot of advantages of practicing electronic games. In conclusion, the majority of electronic games are positive experiences illustrating caring and nurturing behaviors where players earn points for similar positive behaviors.